The stranger the better: support and solidarity in the 2011 students' protests in Chile. (3rd May 2016) - Puga, Ismael
Abstract: This paper analyses the legitimation dynamics of the student protests in Chile 2011, explaining how the support of 'strangers' strengthened its position and endurance. By analysing interviews with both activists and uninvolved citizens, I describe a steady pattern whereby they express the strength and legitimacy of the movement by assessing the 'abstraction' of the link between protesters and their supporters. The more abstract these relations – the stranger supporters are – the most relevant and meaningful is their support. Beyond establishing the worthiness of protesters' claims, strangers provide protesters with a mandate, fostering the movement's cohesion and thus affecting its ability to endure through the conflict. While the literature has mostly looked at adherents as only potential (or failed) constituents, I argue that support that remains external plays a crucial role in social movements' chances of success. This support needs, however, to avoid being framed as insufficient engagement. Further analysis shows that the distinction between protesters and strangers often requires active boundary work, allowing the movement to maximize the benefits of strangers' support while managing its risks. The relation between these boundaries, the efficiency of different contention tactics and their adaptation is analysed here. The study argues that strangeness can involve very different, even opposed phenomena, which are often confounded, namely 'otherness' and 'abstraction'. Critically drawing upon Simmel, I explain how it is 'abstraction' in particular that helps our understanding of the role of strangers in social movements and consider how this distinction could enrich research on the symbolic aspects of contentious politics.